K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 4 2019

(x - 2)(9x + 15) = 0

=> x- 2 = 0 hoặc 9x + 15 = 0

=> x = 2 hoặc 9x = -15

=> x = 2 hoặc x = -15/9 = -5/3

8 tháng 1 2017

a) x+15 = 20-4x

=> x=1

b) 17-x=7-6x

=> x=-2

c) -12+x=5x-20

=> x=2

d) 4x-5=15-x

=> x=4

e) 9x-7=20-6x

=>x= \(\frac{9}{5}\)

g)2.(x-10)=3.(x-20)=x-4

=> x thuộc ∅

h) (x^2+2).(x-3) <0

=> x=3,...

8 tháng 7 2023

a) \(5\left(x-7\right)=0\)

\(\Rightarrow x-7=0\)

\(\Rightarrow x=7\)

b) \(25\left(x-4\right)=0\)

\(\Rightarrow x-4=0\)

\(\Rightarrow x=4\)

c) \(\left(34-2x\right)\left(2x-6\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}34-2x=0\\2x-6=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}2x=34\\2x=6\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=17\\x=3\end{matrix}\right.\)

d) \(\left(2019-x\right)\left(3x-12\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}2019-x=0\\3x-12=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=2019\\3x=12\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=2019\\x=\dfrac{12}{3}=4\end{matrix}\right.\)

e) \(57\left(9x-27\right)=0\)

\(\Rightarrow9x-27=0\)

\(\Rightarrow9\left(x-3\right)=0\)

\(\Rightarrow x-3=0\)

\(\Rightarrow x=3\)

8 tháng 7 2023

a) 5.(x-7)=0⇔x-7=0⇔x=7

b) 25(x-4)=0⇔x-4=0⇔x=4

c) (34-2x).(2x-6)=0

⇔ 34-2x=0 hoặc 2x-6=0

⇔2x=34 hoặc 2x=6

⇔ x=17 hoặc x=3

d) (2019-x).(3x-12)=0

⇔ 2019-x=0 hoặc 3x-12=0

⇔ x=2019 hoặc x=4

e) 57.(9x-27)=0

⇔ 9x-27=0

⇔ x=3

f) 25+(15-x)=30

⇔ 15-x=5

⇔ x=10

g) 43-(24-x)=20

⇔ 24-x=23

⇔ x=1

h) 2.(x-5)-17=25

⇔ 2(x-5)=42

⇔x-5=21

⇔ x=26

i) 3(x+7)-15=27

⇔ 3(x+7)=42

⇔ x+7=14

⇔ x=7

j) 15+4(x-2)=95

⇔ 4(x-2)=80

⇔ x-2=20

⇔ x=22

k) 20-(x+14)=5

⇔ x+14=15

⇔ x=1

l) 14+3(5-x)=27

⇔ 3(5-x)=13

⇔ 5-x=13/3

⇔ x=5-13/3

⇔ x=2/3

3 tháng 4 2017

1) x - 2 = -6

x = -6 + 2

x = -4

2) -5 . x - ( -3 ) =13

-5 . x = 13 + ( -3 )

-5 . x = 10

x = 10 : ( -5 )

x = -2

a) \(\left(x-7\right)\left(x+12\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x-7=0\\x+12=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=7\\x=-12\end{matrix}\right.\)

Vậy: x∈{7;-12}

b) \(\left(3x-15\right)\left(6-2x\right)=0\)

\(3\left(x-5\right)\cdot2\cdot\left(3-x\right)=0\)

hay \(6\left(x-5\right)\left(3-x\right)=0\)

Vì 6≠0

nên \(\left[{}\begin{matrix}x-5=0\\3-x=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=5\\x=3\end{matrix}\right.\)

Vậy: x∈{3;5}

c) \(\left(3x+9\right)\left(4y-8\right)=0\)

\(3\left(x+3\right)\cdot4\left(y-2\right)=0\)

hay \(12\left(x+3\right)\left(y-2\right)=0\)

Vì 12≠0

nên \(\left\{{}\begin{matrix}x+3=0\\y-2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-3\\y=2\end{matrix}\right.\)

Vậy: x=-3 và y=2

d) \(\left(2y-16\right)\left(8x-24\right)=0\)

\(2\left(y-8\right)\cdot8\left(x-3\right)=0\)

hay 16(y-8)(x-3)=0

Vì 16≠0

nên \(\left\{{}\begin{matrix}y-8=0\\x-3=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=8\\x=3\end{matrix}\right.\)

Vậy: y=8 và x=3

e) \(\left(22-11y\right)\left(9x-18\right)=0\)

\(11\left(2-y\right)9\left(x-2\right)=0\)

hay 99(2-y)(x-2)=0

Vì 99≠0

nên \(\left\{{}\begin{matrix}2-y=0\\x-2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=2\\x=2\end{matrix}\right.\)

Vậy: x=2 và y=2

g) \(\left(7y+14\right)\cdot\left(9x-18\right)=0\)

⇔7(y+2)*9(x-2)=0

hay 63(y+2)(x-2)=0

Vì 63≠0

nên \(\left\{{}\begin{matrix}y+2=0\\x-2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=-2\\x=2\end{matrix}\right.\)

Vậy: y=-2 và x=2

h) xy=3

⇒x,y∈Ư(3)

⇒x,y∈{1;-1;3;-3}

*Trường hợp 1:

\(\left\{{}\begin{matrix}x=1\\y=3\end{matrix}\right.\)

*Trường hợp 2:

\(\left\{{}\begin{matrix}x=3\\y=1\end{matrix}\right.\)

*Trường hợp 3:

\(\left\{{}\begin{matrix}x=-1\\y=-3\end{matrix}\right.\)

*Trường hợp 4:

\(\left\{{}\begin{matrix}x=-3\\y=-1\end{matrix}\right.\)

Vậy: x∈{1;-1;3;-3} và y∈{1;-1;3;-3}

i) x*y=-5

⇔x,y∈Ư(-5)

⇔x,y∈{1;-1;5;-5}

*Trường hợp 1:

\(\left\{{}\begin{matrix}x=1\\y=-5\end{matrix}\right.\)

*Trường hợp 2:

\(\left\{{}\begin{matrix}x=-1\\y=5\end{matrix}\right.\)

*Trường hợp 3:

\(\left\{{}\begin{matrix}x=-5\\y=1\end{matrix}\right.\)

*Trường hợp 4:

\(\left\{{}\begin{matrix}x=5\\y=-1\end{matrix}\right.\)

Vậy: x∈{1;5;-1;-5} và y∈{1;5;-1;-5}

k) \(\left(x+4\right)\left(y-5\right)=-3\)

⇔x+4; y-5∈Ư(-3)

⇔x+4; y-5∈{1;3;-3;-1}

*Trường hợp 1:

\(\left\{{}\begin{matrix}x+4=-1\\y-5=3\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-5\\y=8\end{matrix}\right.\)

*Trường hợp 2:

\(\left\{{}\begin{matrix}x+4=1\\y-5=-3\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-3\\y=2\end{matrix}\right.\)

*Trường hợp 3:

\(\left\{{}\begin{matrix}x+4=3\\y-5=-1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-1\\y=4\end{matrix}\right.\)

*Trường hợp 4:

\(\left\{{}\begin{matrix}x+4=-3\\y-5=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-7\\y=6\end{matrix}\right.\)

Vậy: x∈{-5;-3;-1;-7} và y∈{8;2;4;6}

m) (x-9)(y-5)=-1

⇔x-9; y-5∈Ư(-1)

⇔x-9; y-5∈{1;-1}

*Trường hợp 1:

\(\left\{{}\begin{matrix}x-9=1\\y-5=-1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=10\\y=4\end{matrix}\right.\)

*Trường hợp 2:

\(\left\{{}\begin{matrix}x-9=-1\\y-5=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=8\\y=6\end{matrix}\right.\)

Vậy: x∈{10;8} và y∈{4;6}

n) x+3⋮x+4

⇔x+4-1⋮x+4

⇔-1⋮x+4

hay x+4∈Ư(-1)

⇔x+4∈{1;-1}

⇔x∈{-3;-5}

Vậy: x∈{-3;-5}

p)(x-5)⋮x+2

⇔x+2-7⋮x+2

hay -7⋮x+2

⇔x+2∈Ư(-7)

⇔x+2∈{1;-1;7;-7}

hay x∈{-1;-3;5;-9}

Vậy: x∈{-1;-3;5;-9}

17 tháng 7 2019

bài 1:

a) 1/3x=-5/3

x=-5

b) x+12/5=37/15

x=1/15

c) x-1/7=-36/7

x=-5

d) 3x-1/2=0

3x=1/2

x=1/6

e) 2/5+x=1/4

x=-3/20

17 tháng 7 2019

Viết rõ ra hộ mình với

3 tháng 5 2017

a) x = 4

b) x = 2 ; x = -4

c) x = 2 ; x = -15

d) x = 7 ; x = -19

e) x = -4 ; -3 ; -2 ; -1 ; 0

g) x = -1 ; - 2 ; 1 ; 2 ; 3 ; 4 ; ...

Đúng 100% 

Đúng 100%

Đúng 100%

3 tháng 5 2017

a) -12x + 60 + 21 - 7x = 5

-12x - 7x + 60+21 = 5

-19x + 81 = 5

81-5 = 19x

19x = 76

x= 4